DEPRESSION AND LONELINESS IN RURAL OLDER ADULTS LIVING ALONE. (11th November 2018) - Wiese, L; Williams, C L
Abstract: In designing interventions it is important to understand loneliness as explained by rural older adults from diverse cultures living alone. This mixed methods study of older adults living alone in subsidized housing in rural Florida included qualitative interviews and quantitative measures of depression (CES-D), health literacy (REALM-SV), and screening for cognitive impairment (Mini-Cog). Participants were asked open-ended questions about their experience of living alone. Thematic analysis was conducted to construct an explanatory matrix. Participants' age was M =71.5, SD = 6 with low education (M = 8.6, SD = 4.2) and low health literacy (Realm-SV M = 2.9, SD = 2.86). Over ¼ of the sample (n =11) screened positive for cognitive impairment while 15% (n = 6) were depressed (CES-D score >15/60). However, 92% indicated that they were content living alone. Findings help to deepen our understanding of the mental health of an underserved group of rural older adults.